Faktor-faktor yang Memengaruhi Financial Satisfaction Buruh di Kota Surabaya - Cicik Mahmudah Mukhafi (Jurnal Ilmu Manajemen, 2020)
The high value of wages is influenced by the high level of living needs as well. A high standard cost of living can cause financial distress for workers. Individuals with high incomes but dont have any skill to control their financial situation can cause financial problems. Consequently, individual financial satisfaction is low. This study conducted to determine the influence between financial attitude and financial literacy toward financial satisfaction with financial management behavior as a mediating variable. The respondents are 121 workforces from companies in the Rungkut Industry area (SIER) as samples. This research using quota sampling and collecting data by online questionnaires. This study uses Structural Equation Model (SEM) and processed by AMOS 2.4. The result shows that only financial management behavior can affect financial satisfaction. Meanwhile, variable financial attitude, financial literacy can not affect on financial satisfaction. Financial attitude and financial literacy also can not affect on financial management behavior. This study indicated that financial management behavior can not mediate between financial attitude on financial satisfaction and financial literacy on financial satisfaction.